Tenaga Kerja Produksi Dan Non Produksi Padaindustri Makanan Di Indonesia (Production and Non Production Workers on Food Industry In Indonesia) - Wahyuni B., Dian; Bachtiar, Nasri; Elfindri, Elfindri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to determine the role of production and non-production workers in the large and medium-scale food industry in Indonesia and to determine the response of the food industry to the demand for production and non-production labor on changes in several input factors in the production process. The fixed effect model in panel data analysis is performed on secondary data in the form of raw data of the Manufacturing Industry Annual Survey in 2013-2015. Demand for production and non-production labor is obtained through the derivation of the production function of Constant Elasticity of Substitution (CES). The results showed that non-production labor had a positive and significant effect on output in all industrial categories, while production labor had only a positive and significant effect on the overall industry category, non-export oriented and located in regions outside of Java. Production and non-production workers are complementary. Demand for production and non-production labor is affected by changes in wages, respectively. The food industry is labor intensive and applies a high wage system (efficiency wage theory).